Proteostasis and Chaperone Surveillance - Singh, Laishram Rajendrakumar; Dar, Tanveer Ali; Ahmad, Parvaiz (Springer India : Imprint: Springer, 2015)
Proteostasis is central to the development of various human diseases caused due to excessive protein misfolding and the disregulation of the protein quality control system. In this book, respected researchers from many leading institutions contribute their insights on proteostasis maintenance. The coverage mainly focuses on the basics of maintaining proteostasis, the consequences of proteostatic system failure, and how chaperone systems constantly maintain proteostasis. In addition, the book presents in detail different treatment strategies for diseases caused by proteostatic system failure, as well as the inhibition of proteostatic failure using small molecule compounds. It examines advances in the modulation of proteopathies, providing a comprehensive source of key mechanistic insights on these diseases. As such, the book offers a valuable resource for beginners and more experienced investigators alike who are looking for detailed and reliable information on protein homeostasis, the diseases that can develop due to related imbalances, and the essential role of molecular and chemical chaperones.